Instagram as a Media for Digital History Literacy: Content Analysis of Instagram Account @historiadotid - Kusmayadi, Yadi; Nurrohmah, Ahliha; Silviani, Pani (Universitas Galuh, 2025)
This study aims to analyze the Instagram account @historiadotid as a medium for historical literacy in the digital era. The background of this study is the shift in the way people, especially the younger generation, access historical information from conventional media to social media. The research uses the netnography method, through analyzing the posts, captions, and responses of the account's followers. The results show that @historiadotid consistently uploads daily content in the form of infographics and video reels that present history in a visual, concise and educative manner. The communicative narrative style, the use of credible sources, and the two-way interaction between account managers and followers show that social media can be an inclusive and critical means of learning history. Followers' responses in the form of appreciation, discussion and clarification indicate the existence of a dialogical historical literacy space in the digital realm. The main contribution of this research is to provide an understanding of the strategy of using social media in strengthening historical literacy. The implication is that social media, especially Instagram, has the potential to become an inclusive, participatory and contextual history education space, especially for young people who are attached to digital culture.